Pengaruh lingkungan sosial dan keputusan penggunaan uang elektronik terhadap perilaku konsumtif (studi pada mahasiswa fisip universitas lampung yang berbelanja secara online) - sebriyanti, lutfi (Jurnal Kompetitif Bisnis, 2021)
This study aims to determine the influence of social environment, and the use of money on consumptive behavior among FISIP students at Lampung University who are seen online. This type of explanatory research with a quantitative approach. The population in this study were online students of the Faculty of Social and Political Sciences at the University of Lampung. The sampling technique used purposive sampling with a sample of 100 respondents. The data were obtained from a questionnaire using a Likert scale. Data analysis in this study using multiple linear regression analysis. The results of the study explained that the social environment, and the decision to use electronic money were significantly related to the consumer behavior of online students of the Faculty of Social and Political Sciences, Lampung University The simultaneous test results show that the effect of concepts, social environment, and decisions on the use of electronic money has an effect on consumptive behavior among FISIP students at Lampung University who are online. Keywords : Social Environment, Decision on the Use of Electronic Money, Consumptive Behavior